North Atlantic Islands and a complicated wedding in Egils saga - Barreiro, Santiago Francisco (2023)
This article discusses the role of the Northern Islands in an episode of Egils saga, a medieval Icelandic text written during the first half of the thirteenth century. The episode focuses on the complexities of a wedding in which the involved groups do not have an initial agreement, developing into a conflictive situation spanning into several lands and agents. The resolution of said conflict, which involves some of the major characters in the saga, leads to a discussion of the concept of “liminality”. Its possibilities and limits for the analysis of Norse societies are here assessed through this case study.